2002
DOI: 10.1016/s0014-5793(02)03587-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet ERK2 activation by thrombin is dependent on calcium and conventional protein kinases C but not Raf‐1 or B‐Raf

Abstract: Extracellular signal-regulated kinase (ERK) activation pathways have been well characterized in a number of cell types but very few data are available for platelets. The thrombin-induced signaling pathway leading to ERK2 activation in platelets is largely uncharacterized. In this study, we investigated the kinases involved in thrombin-induced ERK2 activation in conditions of maximal ERK2 activation. We found that thrombin-induced mitogen-activated protein kinase/ERK kinase (MEK)1/2 activation was necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 40 publications
(52 reference statements)
7
66
0
4
Order By: Relevance
“…Thrombin activated ERK in the endothelial cells (57). While this report was being revised, it was reported that thrombin activated p38 kinase in the platelets, which led to NF-B-dependent leukocyte recruitment (58).…”
Section: Discussionmentioning
confidence: 93%
“…Thrombin activated ERK in the endothelial cells (57). While this report was being revised, it was reported that thrombin activated p38 kinase in the platelets, which led to NF-B-dependent leukocyte recruitment (58).…”
Section: Discussionmentioning
confidence: 93%
“…Raf-MEK1/2-ERK1/2 has been shown to be a classical pathway for ERK1/2 activation in various physiological and pathological processes 32 ; however Nadal-Wollbold et al reported that the activation of platelet ERK2 was independent of Raf. 33 Also, our recent studies demonstrated that Raf was responsible for platelet ERK5 activation. 34 MLK3 has been reported to activate JNKs and regulate apoptosis and dorsal closure during embryonic morphogenesis, 35,36 suggesting that MLK3 might play a synergistic role in MEKK3-mediated JNK2 activation in platelets.…”
Section: Discussionmentioning
confidence: 97%
“…Our results indicate that the latter is the case in HCs, because in our studies Raf was not involved in MEK-ERK activation in these cells. Such Ras/Raf-independent activation of MEK-ERK is known to occur in other cell types stimulated with different stimuli (Hindley and Kolch, 2002;Nadal-Wollbold et al, 2002).…”
Section: Discussionmentioning
confidence: 99%